NILAI-NILAI ISLAMI DALAM NOVEL API TAUHID KARYA HABIBURRAHMAN EL SHIRAZY: KAJIAN SOSIOLOGI SASTRA - Suharso Suharso (EDU-KATA, 2020)
The purpose of this study is to describe the values of faith, worship, and morals contained in the novel Api Tauhid by Habiburrahman El-Shirazy. This researchis a type of qualitative research, which is a study that does not use calculation of numbers. In this study researchers used library research. In collecting data usingdocument review techniques or commonly called documentation analysis. Data analysis in this study through three stages, including: data reduction, data presentation, and conclusion. Islamic values contained in the novel Api Tauhid include: the values of the faith which include planting the value of faith, faith in God, faith in the destiny of Allah, and faith in the last day. The values of worship include prayer on time, guarding against immoral acts, recitation, prayer, and preaching. Moral values include respect for parents, respect for experts, respect for the government, inferiority, courtesy, and honesty.